Supportive nurse-midwife care is associated with a reduced incidence of cesarean section - Butler, Jane; Abrams, Barbara; Parker, Jennifer; Roberts, James M.; Laros, Russell K. (American journal of obstetrics and gynecology, 1993)
OBJECTIVE: Our purpose was to examine whether care by a certified nurse-midwife, including personal labor support, was associated with a reduced risk of cesarean delivery. STUDY DESIGN: A retrospective cohort study comparing 3551 physician-managed patients with 1056 certified nurse-midwife—managed patients in a university hospital with a mixed socioeconomic and ethnic population was performed. Regression analysis was used to estimate the risk of labor abnormalities, diagnosis of fetal distress, and cesarean delivery in patients delivered by a certified nurse-midwife vs a physician and to control for maternal age, race, parity, fetal size, and delivery year. Subjects included were women having at least five prenatal visits who were delivered of term, singleton, liveborn infants without congenital anomalies with occiput presentation. RESULTS: Odds ratio for cesarean section for women delivered by certified nurse-midwives versus those delivered by physicians was 0.71 (95% confidence interval 0.55, 0.91). Midwifery care was associated with a lower risk of abnormal labor (adjusted odds ratio 0.70, 95% confidence interval 0.60, 0.83) and diagnosis of fetal distress (adjusted odds ratio 0.50, 95% confidence interval 0.32, 0.77) CONCLUSION: This work demonstrates that labor abnormalities and diagnosis of fetal distress are less frequent in patients cared for by nurse-midwives, and there is an association with a lower incidence of cesarean section.